The Effect of Using the Experiential Learning Model and Environmental Vocabulary Mastery on Poetry Writing Skills - Dedi Saputra; Vasmia S Damayanti; Yeti Mulyati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze students' abilities writing poetry texts with vocabulary mastery in the environmental field is influenced by the experiential learning model. This type of research uses quantitative methods  experimental design. population 130 students. Sampling was done purposively as many as 22 people sampling technique in class X MIPA I, experimental class, and 22 people in class X MIPA 2, namely the control class. The results showed that the experimental class taught by experiential learning model was better than the control class taught by conventional methods. This can be seen from the results of th tt, meaning that there is a significant influence between the experiential learning model on the ability to write poetry texts of students. Students' ability in writing poetry texts and high environmental vocabulary mastery using experiential learning models is better than students' high environmental vocabulary mastery using conventional methods. The ability to write poetry texts of students with low environmental vocabulary mastery using the experiential learning model is better than students with low environmental vocabulary mastery using conventional methods. There is no interaction between the experiential learning model and environmental vocabulary mastery in influencing students' ability to write poetry texts.